Teachers’ Misconception about National Assessment and National Examination - Kisno Kisno; Umi Rokhyati; Fenty Nur Fatimah; Rita M Siregar (Universitas Ahmad Dahlan, 2021)
National Assessment is administered as the new policy from The Ministry of Education and Culture of Indonesia. It will be administered from September to October 2021. Therefore, teachers are urged to master the concept and the format of national assessment so as to implement it in the learning process. The teachers’ proper understanding on those concept and formats supports the success of national assessment. Despite this fact, most of the teachers were fulfilled with anxiety of the transition from national examination to national assessment. This research attempted to reveal the junior high school teachers’ misconception about National assessment and national examination. A 30-online-multiple-choice test was administered to 50 in-service teachers from both the state and the private junior high schools. The data was analyzed using descriptive statistics. The findings revealed that both the state and the private junior high schools’ teachers experienced three misconceptions about national assessment. Majority of the teachers’ misconception was about the technical administration of national assessment (76%) and the others were about the basic concept of national assessment (65%), and the follow up to result of national assessment (61%). These results suggest the reinforcement and empowerment of the schools concerning the socialization and the prototype or simulation implementation of national assessment.